2016
DOI: 10.1016/j.ejca.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-human phase I study of the oral Notch inhibitor, LY900009, in patients with advanced cancer

Abstract: The recommended MTD schedule for future studies was 30 mg thrice weekly, which exceeds the target inhibition level observed in preclinical models to promote tumour regression in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 43 publications
(32 reference statements)
2
39
0
1
Order By: Relevance
“…molecular regulators of EMT/CSCs such as Notch4 , Twist4 , YAP1 , and CD44/c‐Met . For some of these targets, investigational drugs are available . For example, a novel compound that has Nodal and Notch4 as major targets and that blocks VM in vitro is under clinical development .…”
Section: Discussionmentioning
confidence: 99%
“…molecular regulators of EMT/CSCs such as Notch4 , Twist4 , YAP1 , and CD44/c‐Met . For some of these targets, investigational drugs are available . For example, a novel compound that has Nodal and Notch4 as major targets and that blocks VM in vitro is under clinical development .…”
Section: Discussionmentioning
confidence: 99%
“…DAPT, a γ-secretase inhibitor, which reduces gamma-secretase in Notch1 signaling pathway was reported as a highly promising novel therapeutic drug candidate for ovarian cancer patient [21]. LY900009, a first-in-human phase I study of the oral Notch inhibitor was also reported in patients with advanced cancer including ovarian cancer [22]. MK-0752 is another novel γ-secretase inhibitor, which is evaluated in clinical trial for treatment of several types of cancer including ovarian cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the Notch pathway via γ ‐secretase inhibitors prevents notch receptor cleavage at the cell surface, and blocks activation of self‐renewal target genes. Currently, γ ‐secretase inhibitors RO4929097, LY900009 and PF‐003084014 are being used in independent clinical studies against breast cancer, ovarian cancer and T cell acute lymphoblastic leukaemia and alzheimer's respectivelyHowever, it is evidently reported in rodents that these inhibitors caused abnormalities in the gastrointestinal tract, thymus and spleen. These toxic effects were due to prolonged use of these inhibitors causing malfunctioning in cell fate decisions .…”
Section: Notch Signalling and Recent Developments In Therapeutic Apprmentioning
confidence: 99%